PENERAPAN PENGUATAN POSITIF TERHADAP KETERLIBATAN PERILAKU SISWA DALAM PEMBELAJARAN JARAK JAUH [THE IMPLEMENTATION OF POSITIVE REINFORCEMENT ON STUDENTS’ BEHAVIOR IN DISTANCE LEARNING] - Deosari, Ardine; Appulembang, Oce Datu (JOHME: Journal of Holistic Mathematics Education, 2022)
Student engagement is a manifestation of the responsibility of students as humans to God. Humans have responsibility to be involved in caring for and protecting the earth (Gen. 1:28). So, it is fitting for students to be involved in every process of their life, including learning. Distance learning is negatively affected when students are late joining the video conference, are mostly silent when the teacher asks questions, do not listen to teacher instructions properly which causes them not to return to the video conference, and do not answer when called on by the teacher. Positive reinforcement is given to stimulate and increase student motivation, increase student attention in the learning process, and increase student learning activities. The purpose of this study is to describes the application of positive reinforcement methods on the involvement of student behavior in distance learning and see the positive impact. The research method used is descriptive qualitative. Based on the research, it was found that by applying four forms of positive reinforcement according to the principles of warmth and enthusiasm, meaningfulness, avoiding negative responses, and using various positive reinforcements, students can be encouraged in their behavior and involvement in learning. It also encourages other aspects, such as student discipline, student creativity, student confidence, and student learning attitudes.BAHASA INDONESIA ABSTRACT: Keterlibatan siswa merupakan salah satu perwujudan tanggung jawab siswa sebagai manusia kepada Allah. Manusia memiliki tanggung jawab untuk terlibat dalam memelihara dan menjaga bumi (Kej 1:28). Maka, sudah sepatutnya siswa terlibat dalam setiap proses kehidupannya, termasuk dalam pembelajaran. Pada kenyataannya, siswa terlambat bergabung di video conference, perilaku siswa sebagian besar diam ketika guru bertanya, tidak mendengarkan instruksi guru dengan baik dan menyebabkan siswa tidak kembali bergabung di video conference, dan tidak menjawab ketika ditunjuk oleh guru. Penguatan positif diberikan untuk merangsang dan meningkatkan motivasi belajar siswa, meningkatkan perhatian siswa dalam proses pembelajaran, dan meningkatkan aktivitas belajar siswa. Tujuan dari penelitian ini ialah untuk memaparkan penerapan metode penguatan positif terhadap keterlibatan perilaku siswa pada pembelajaran jarak jauh dan melihat dampak positifnya. Metode penelitian yang digunakan ialah deskriptif kualitatif. Berdasarkan penelitian ditemukan bahwa, dengan menerapkan empat bentuk penguatan positif sesuai prinsip kehangatan dan antusias, kebermaknaan, menghindari respon negative dan menggunakan penguatan positif yang bervariasi dapat mendorong keterlibatan perilaku siswa dalam pembelajaran. Hal ini juga mendorong aspek lain yang terdapat pada diri siswa, seperti kedisiplinan siswa, kreativitas siswa, kepercayaan diri siswa, dan sikap belajar siswa.